Evaluating the Effectiveness and Cost Effectiveness of Social Welfare and Economic Growth Programs - Wahyuni, Wahyuni; Ananda, Dea Rezki; Destiana, Gloria (Scieclouds Publishing, 2024)
This research assesses the efficiency, cost-efficient, and relevancy of the programs that have been put in place to address social welfare and economic growth with the use of quantitative measure. With an insight from various programs such as healthcare reforms, entrepreneurship support, infrastructure projects and social safety nets among others, the study determines the various aspects that influence the success of a program. The outcomes show that the four health care reforms and the six-entrepreneurship support are the optimum and efficient programmed displaying mean utility score of 4. 25 and 4. 15, respectively. On the other hand, the infrastructure projects and the social safety nets have comparatively lower effectiveness scores which indicate potential areas of improvement. Based on the cost analysis done, it is clear that the ministry can get the highest economic return by supporting entrepreneurship support prompting the need to support it. The study also shows that there have been great strides in the use of programmed evaluation through integration of advanced technologies like artificial intelligence and big data analytics. These technologies increase the effectiveness, efficiency and credibility of assessing the impact of program. Besides, the research supports that programs are well-aligned with Sustainable Development Goals (SDGs) in the context of healthcare reforms and entrepreneurship. The research presented here covers for similar research works by giving a comprehensive quantitative comparison of different types of programs so as to inform improvement on program deployment among the policymakers. The results help to gain more insights into program performance and generate practical suggestions that can help in obtaining and expanding the successful societal impact.